EDUKASI OBAT RUSAK DAN KEDALUARSA PADA MASYARAKAT DESA TOSALE, KECAMATAN BANAWA SELATAN, KABUPATEN DONGGALA - diana, khusnul; Rinaldhi Tandah, Muhamad; Ambianti, Nurul; Fadhilah Zainal, Setiawati (Jurusan Farmasi FMIPA Universitas Tadulako, 2022)
Using damaged and expired drugs in the community can be a problem for health. Using medicines that have been damaged or drugs that have expired can be fatal, ranging from poisoning, and disability, to causing death. Many factors can cause damaged and expired drugs, both occurring in health facilities (such as pharmacies, hospitals, health centers, and distributors) or the storage of drug users in this case in the community. People as users of medicinal products sometimes do not know how the physical characteristics and signs of drugs are damaged and medicines that have expired. This community service activity was carried out in the Tosale Village area of ​​Donggala to assist the local community in knowing and recognizing drugs that were damaged or expired. This activity is carried out using lecture and discussion methods around recognizing the characteristics and signs of damaged and expired drugs, how to prevent the occurrence of damaged and expired drugs and how to store medicines to avoid damage. Evaluation of activities by giving short questions to participants about the material that has been given to identifying damaged and expired drugs. Active participants who answered correctly were given the appreciation in the form of mementos from the service team. This activity was completed by the target number of participants and the time given by the Tosale Village Head.